Spartacus. (Brighton : JDS Publications.)
Fonds Suzan Daniel (FSD)
F/02/016 Archief Roger Vertongen
Periodiciteit : maandelijks
Redactie : JDS Publications, 46 Preston Street, Brighton
Engels
Periodiek